If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + 12 = -2 Reorder the terms: 12 + -2a = -2 Solving 12 + -2a = -2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2a = -2 + -12 Combine like terms: 12 + -12 = 0 0 + -2a = -2 + -12 -2a = -2 + -12 Combine like terms: -2 + -12 = -14 -2a = -14 Divide each side by '-2'. a = 7 Simplifying a = 7
| 3(x+6)=4x-x+2 | | 3.1m=-12.4 | | 216=w^3 | | 9d-18=58 | | 3.1m=-12.5 | | 60+5n=2n | | 5x-10=5(x+4) | | 5w-27=28 | | 4=-2g | | .4n=12 | | -x/24=4 | | 2c+(3c+-4)=5c+-4 | | 6=r-7 | | y=9x+3x | | Z-5-13= | | X+(-8)=-16 | | 3y+15=36 | | 2c+(3c+-4)=4c+-4 | | -4(n+2)=-5n | | (8x^4y^2/3z^3)*(9xy^2z^6/4y^4) | | 1.21=11(0.5+0.4x)whatisx | | -33/4x=-60 | | 12*x=132 | | 8+4v+8v+5=1+8v | | (8x^4y^2/3z^3)*(9xy^2z^6) | | 4a+3b+8-2a-3b= | | 3x-54=44+10x | | 5x+4-x=4+3x-4 | | 3(x-6)=4x-x+2 | | 7x+9=x-3y | | 2x+(2b-1)y=4 | | 23-48x=82x+56 |